Chewing induced reflex seizures ("eating epilepsy") and eye closure sensitivity as a common feature in pediatric patients with SYNGAP1 mutations: Review of literature and report of 8 cases. (February 2019) - von Stülpnagel, Celina; Hartlieb, Till; Borggräfe, Ingo; Coppola, Antonietta; Gennaro, Elena; Eschermann, Kirsten; Kiwull, Lorenz; Kluger, Felicitas; Krois, Ilona; Møller, Rikke S.; Rössler, Franziska; Santulli, Lia; et al.
Highlights: Chewing induced reflex seizures seem to be common in pediatric SYNGAP1 patients. Ictal EEG points to the posterior cortex as hub for chewing induced reflex seizures. Eyelid myoclonia was the most common seizure type, typically induced by eye closure. If eye closure sensitivity is part of complex trigger mechanism is to be elucidated. Abstract: Purpose: Heterozygous SYNGAP1 gene mutations have been associated with several forms of idiopathic generalized epilepsy, autism spectrum disorders and delay of psychomotor development. We report eight patients with a SYNGAP1 mutation and chewing/eating induced reflex seizures as new phenotype and compare them to other patients with eating epilepsy and genetic mutations. Methods: Presentation of clinical and anamnestic features and retrospective analysis of Video-EEG data of a 4 year old index patient with SYNGAP1 mutation and chewing /eating induced seizures. Clinical and anamnestic features and home videos of seven additional patients (4 female; age: 4–14 years) with SYNGAP1 mutation and eating induced reflex seizures were compared. Results: All reflex seizures of the index patient showed similar focal EEG pattern with 1–5 seconds high amplitude, irregular 3/sec spike-wave complexes with initiation from left temporo-occipital, right temporo-occipital or bi- occipital / temporo-occipital regions. Eyelid myoclonia, the most common seizure type in all 8 patients, were typically initiated by eating or other simple orofacial stimuli. In the index patient eye closure preceded eating induced-eyelid myoclonia in 30/38 seizures. Conclusion: The main clinical features of our patient (i.e. intellectual disability, epilepsy, autistic features) are compatible with previous reports on patients with SYNGAP1 mutations. This is the first complete description of eating induced seizures in association with SYNGAP1 mutations. Whether eye closure sensitivity (ECS) represents an independent reflex epileptic trait, as seen in other patients with idiopathic "generalized" epilepsies (IGE), or eye closure is part of a complex trigger mechanism in SYNGAP1 patients' remains to be elucidated.